Dinamika Ijtihad Nahdlatul Ulama (Analisis Pergeseran Paradigma dalam Lembaga Bahtsul Masail NU) - Muhammad Ulil Abshor (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
When the progressive groups argues renewal to break the stagnation of ijtihad experienced by Muslims, NU still strictly declares as a group which has mazhab. It does not mean that NU rejects ijtihad, but NU precisely has a new direction in its ijtihad concept. Initially, NU more emphasizes on ijtihad qouli or text paradigm, which leans on the opinion of mazhab leader, but at the conference in Bandar Lampung (1994), NU made a new breakthrough by deciding to do ijtihad by using manhaji or reason paradigm, which is still using the pattern and method applied by mazhab leader. The ijtihad model developed by NU is ijtihad which remains appreciative to the works of previous scholars, and without insists the developing dynamics in society. Thus can be interpreted as an attempt of NU to be not stuck in